(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This study aimed to identify the effectiveness of electronic formative assessment based on two types of feedback (explanatory and corrective) and its impact on academic achievement and test anxiety among third-year secondary female students in mathematics in the city of Jeddah. A quasi-experimental design was used as an experimental method. The research sample consisted of 64 students, divided into two groups: a control group that received corrective feedback, and an experimental group that received explanatory feedback. The study tools included a pre- and post-cognitive test and a test anxiety questionnaire developed by Dr. Mohammed Al-Tayeb. The research results showed statistically significant differences between the mean post-test scores for the experimental and control groups in favour of the experimental group. The results also revealed statistically significant differences between the mean test anxiety scores of the control and experimental groups in favour of the experimental group, indicating the effectiveness of formative assessment in reducing students’ test anxiety.